Replicating Europe’s Normative Power: Challenges and Pathways for South Asia's Regional Integration - Adeel Kazmi (NUST Journal of International Peace and Stability)
European nations attained stability and integration by overcoming a turbulent history marked by deeply entrenched conflicts and the profound devastation of two world wars.  Europe has evolved into a ‘normative power’ and the European Union into a ‘community of practice’ by overcoming statism and establishing responsive institutions and systems of accountability. Europe’s transformation reflects the practical application of normative principles. In contrast, South Asia grapples with political instability and geo-strategic challenges that impede regional integration. This paper identifies the key obstacles to political connectivity and adopting normative practices in South Asia. It further explores potential pathways, enabling the region to draw lessons from Europe’s experience and develop into a community of practice and a normative power.